Bridging Zambia's water service gap: NGO/community partnerships - Sam Kayaga; Cathryn Kadimba-Mwanamwambwa (2006)
Although the world's urban population has in the last 50 years increased fourfold, investment in water and sanitation services infrastructure in low-income countries has not kept pace with this population growth. Consequently, between 30 and 60% of the urban population is not adequately served. Invariably, poor people bear a disproportionate share of the impact of low service levels and are forced to adopt coping mechanisms, ranging from group connections to reliance on traditional water supply and sanitation systems, which are often technically unsuitable to the urban environment. This paper presents a case study in which CARE International set up an independent community-managed ‘Water Trust’ system to serve about 85 000 people in Kanyama, a low-income settlement in Lusaka, Zambia. A recent evaluation study showed that, compared to services delivered by Lusaka Water and Sewerage Company, the legitimate water utility, the Water Trust system was delivering water services of better quality and in a cost-effective manner. Further study needs to be done on the optimum institutional arrangement to ensure that communities served by the Water Trust fully benefit from the regulatory regime currently taking a firm grip in Zambia.